2018
DOI: 10.1177/0146167218796790
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Luxury: Social Costs of Luxury Consumption

Abstract: Extant research demonstrates that luxury goods are beneficial signals that bestow upon individuals social benefits that range from positive evaluations to compliance. In contrast to this perspective, the current work explores the idea that luxury goods can carry significant negative social costs for actors. Across four experiments, the social cost of luxury is examined. Although individuals who display luxury goods are ascribed higher status, they can pay a hefty tax when it comes to warmth. The social costs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 46 publications
5
61
1
2
Order By: Relevance
“…Despite certain benefits associated with luxury consumption, such as attribution of status, preferential treatment, and affiliation with desirable social groups and mates (Bellezza and Berger 2020;Griskevicius et al 2007;Veblen 1899), recent work documents many social costs associated with the consumption of high-end, expensive products. For example, consumers who own luxury goods are considered less warm and authentic and more driven by impression-management motives than consumers who do not own them (Cannon and Rucker 2019;Ferraro, Kirmani, and Matherly 2013;Garcia, Weaver, and Chen 2018;Goor et al 2020). These negative perceptions may also be driven by a failure to consider the durability of high-end products at the observers' end.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Despite certain benefits associated with luxury consumption, such as attribution of status, preferential treatment, and affiliation with desirable social groups and mates (Bellezza and Berger 2020;Griskevicius et al 2007;Veblen 1899), recent work documents many social costs associated with the consumption of high-end, expensive products. For example, consumers who own luxury goods are considered less warm and authentic and more driven by impression-management motives than consumers who do not own them (Cannon and Rucker 2019;Ferraro, Kirmani, and Matherly 2013;Garcia, Weaver, and Chen 2018;Goor et al 2020). These negative perceptions may also be driven by a failure to consider the durability of high-end products at the observers' end.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…For example, they buy a Hublot Big Bang watch for US $ 5 million but this item looks ordinary to those below. This class uses luxury products to serve as a signal of elegance and good taste (Cannon andRucker 2018, Han et al 2010). They signal their status in abstract ways, which are difficult to recognize by those below.…”
Section: Discussionmentioning
confidence: 99%
“…However, this will affect their long term living standard as they must cut down on their basic needs such as food, education, and health. Cannon & Rucker (2019); Chakravarti (2006) indicated that long-term status consumption will put them into debt and poverty. Unfortunately, such aspiration for conspicuous consumption negatively impacts their long-term financial sustainability and their areas of priority (Matos, 2019, Kaufman, 2018.…”
Section: Consequences Of Conspicuous Consumptionmentioning
confidence: 99%